The London money market - Shaw, E. R. (London : Heinemann, 1975)
The purpose of this book is to provide a rigorous examination of the London money market from 1959 to 1973.
Includes index.
Bibliography: p. [225]-227.
osc 11/07/2018
Loans
Keywords: Money market